Association Among Local Hemodynamic Parameters Derived From CT Angiography and Their Comparable Implications in Development of Acute Coronary Syndrome - Yang, Seokhun; Choi, Gilwoo; Zhang, Jinlong; Lee, Joo Myung; Hwang, Doyeon; Doh, Joon-Hyung; Nam, Chang-Wook; Shin, Eun-Seok; Cho, Young-Seok; Choi, Su-Yeon; Chun, Eun Ju; Nørgaard, Bjarne L.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Association among local hemodynamic parameters and their implications in development of acute coronary syndrome (ACS) have not been fully investigated. Methods: A total of 216 lesions in ACS patients undergoing coronary CT angiography (CCTA) before 1–24 months from ACS event were analyzed. High-risk plaque on CCTA was defined as a plaque with ≥2 of low-attenuation plaque, positive remodeling, spotty calcification, and napkin-ring sign. With the use of computational fluid dynamics analysis, fractional flow reserve (FFR) derived from CCTA (FFRCT) and local hemodynamic parameters including wall shear stress (WSS), axial plaque stress (APS), pressure gradient (PG) across the lesion, and delta FFRCT across the lesion (ΔFFRCT) were obtained. The association among local hemodynamics and their discrimination ability for culprit lesions from non-culprit lesions were compared. Results: A total of 66 culprit lesions for later ACS and 150 non-culprit lesions were identified. WSS, APS, PG, and ΔFFRCT were strongly correlated with each other (all p < 0.001). This association was persistent in all lesion subtypes according to a vessel, lesion location, anatomical severity, high-risk plaque, or FFRCT ≤ 0.80. In discrimination of culprit lesions causing ACS from non-culprit lesions, WSS, PG, APS, and ΔFFRCT were independent predictors after adjustment for lesion characteristics, high-risk plaque, and FFRCT ≤ 0.80; and all local hemodynamic parameters significantly improved the predictive value for culprit lesions of high-risk plaque and FFRCT ≤ 0.80 (all p < 0.05). The risk prediction model for culprit lesions with FFRCT ≤ 0.80, high-risk plaque, and ΔFFRCT had a similar or superior discrimination ability to that with FFRCT ≤ 0.80, high-risk plaque, and WSS, APS, or PG; and the addition of WSS, APS, or PG into ΔFFRCT did not improve the model performance. Conclusions: Local hemodynamic indices were significantly intercorrelated, and all indices similarly provided additive and independent predictive values for ACS risk over high-risk plaque and impaired FFRCT.